Changes or disappearance of the Atlantic goliath grouper Epinephelus itajara (Perciformes: Epinephelidae) spawning aggregation sites in southern Brazil - Leonardo Schlogel Bueno; Matheus Oliveira Freitas; Áthila Andrade Bertoncini; Christopher Carl Koenig; Johnatas Adelir-Alves; Jonas Rodrigues Leite; Felipe Alexandre de Lisboa Miranda Daros; Maurício Hostim-Silva (Neotropical Ichthyology, 2025)
Abstract Atlantic goliath grouper (Epinephelus itajara) form spawning aggregations, each with around 100 individuals. However no studies have been carried out comparing these aggregations in natural and artificial environments. In this article we determine patterns in aggregation abundance by observations we made between 2007 and 2014 on three natural and four artificial reefs in southern Brazil by comparing sightings-per-unit-effort (SPUE) among these reefs. Their abundance differed significantly among artificial and natural reefs. No aggregations were observed on natural reefs, however aggregations up to 54 atlantic goliath groupers were observed on artificial reefs. This changed pattern of abundance may be due to fishing pressure and/or attraction to artificial reefs. We discuss the potential ecological effects of diminished abundance on natural reefs and increased abundance on artificial reefs.